A high-speed MIM resistive memory cell with an inherent vanadium selector. (December 2020) - Lin, Chih-Yang; Tseng, Yi-Ting; Chen, Po-Hsun; Chang, Ting-Chang; Eshraghian, Jason K.; Wang, Qiwen; Lin, Qi; Tan, Yung-Fang; Tai, Mao-Chou; Hung, Wei-Chun; Huang, Hui-Chun; Lu, Wei D.; et al.
Highlights: We propose a simple 3-layer MIM structure to construct a 1-Selector-1-RRAM device with ultrafast switching speed, low forming voltage and switching voltage. This novel 1S1R device shows good performance and high reliability for future application in both high lateral and vertical density integration in crossbar arrays. Complete electrical measurement, material analyses and simulations are undertaken, to characterize the fabricated 1S1R device. A simple structure with vanadium as the electrode and indium tin oxide as the switching layer to form a built-in low subthreshold selector. The physical models based on simulations are developed to explain the coexistence for the selector and resistive switching. Abstract: Resistive random-access memory (RRAM) structured in crossbar arrays typically use selectors to improve noise margins by suppressing sneak path currents and leakages. Without selectors, crossbar array dimensions would be prohibitively small for practical use in storage-class memory (SCM), and compute-in-memory (CIM) applications. Most one-selector one-resistor (1S1R) memory cells fabricate the selector and RRAM independently. Here, an extremely simple process is presented to construct a 1S1R cell consisting of a metal-insulator-metal (MIM) structure of V/ITO(O2 )/TiN, where the unique electrical properties of vanadium form a built-in selector. High vertical stacking density is achieved by removing the need for a separate series-connected selector. Threshold switching (TS) based on metal-insulator transition (MIT) in the vanadium top electrode (TE) selector is observed with a subthreshold swing of under 30 mV/dec. The selector is directly integrated with indium tin oxide (ITO) which provides low-voltage/high-speed resistive switching behavior (set process of <30 ns, reset of <50 ns). The use of ITO as a low- k switching layer is expected to concentrate electric fields which forms narrow conduction pathways, resulting in low forming voltages, fast switching speeds, and inherent current suppression when acting as a selector.